Nanomaterial-Based Zinc Ion Interference Therapy to Combat Bacterial Infections - Wei, Yongbin; Wang, Jiaming; Wu, Sixuan; Zhou, Ruixue; Zhang, Kaixiang; Zhang, Zhenzhong; Liu, Junjie; Qin, Shangshang; Shi, Jinjin (Frontiers in Immunology, 2022)
Pathogenic bacterial infections are the second highest cause of death worldwide and bring severe challenges to public healthcare. Antibiotics resistance makes it urgent to explore new antibacterial therapy. As an essential metal element both in humans and bacteria, zinc ion has various physiological and biochemical functions. They can stabilize the folded conformation of metalloproteins and participate in critical biochemical reactions, including DNA replication, transcription, translation, signal transduction, etc. Therefore, zinc deficiency would impair bacterial activity. Interestingly, the excessive zinc ions also could cause oxidative stress to damage DNA, proteins, and lipids by inhibiting the function of respiratory enzymes to promote the formation of free radicals. Such dual characteristics endow zinc ions with unparalleled advantages in the direction of antibacterial therapy. Based on the fascinating features of zinc ions, nanomaterial-based zinc ion interference antibacterial therapy emerges relying on the outstanding benefits of nanomaterials. Zinc ions interference therapy is clearly divided into two classes: zinc overloading and zinc deprivation. In this review, we summarized the recent innovative zinc ions interference strategy for the treatment of bacterial infections and focused on analyzing the antibacterial mechanism of zinc overloading and zinc deprivation. Finally, we discuss the current limitations of zinc ions interference antibacterial therapy and put forward problems of clinical translation for zinc ions interference antibacterial therapy.